Polymer based nanoparticles for biomedical applications by microfluidic techniques: from design to biological evaluation. Issue 46 (15th November 2021) - Fabozzi, Antonio; Della Sala, Francesca; di Gennaro, Mario; Solimando, Nicola; Pagliuca, Maurizio; Borzacchiello, Assunta
Abstract : The development of microfluidic technologies represents a new strategy to produce and test drug delivery systems. Abstract : The development of microfluidic technologies represents a new strategy to produce and test drug delivery systems. In particular, microfluidics can facilitate the development of new nanoparticle-based systems with controlled physicochemical properties and evaluate their efficiency and efficacy in in vitro biomimetic models of human organs (organ-on-a-chip). Microfluidics shows promising effective potential for the preclinical testing of nanoparticle-based drug delivery systems compared to the traditional in vitro cell culture. In this review, we present a detailed state-of-the-art based on the microfluidic technologies focusing on the synthesis, industrial scale-up, and biological characterization of polymeric nanoparticles for drug delivery applications.